2018
DOI: 10.1530/rep-18-0009
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic reprogramming during spermatogenesis and male factor infertility

Abstract: Infertility is an often devastating diagnosis encountered by around one in six couples who are trying to conceive. Moving away from the long-held belief that infertility is primarily a female issue, it is now recognised that half, if not more, of these cases may be due to male factors. Recent evidence has suggested that epigenetic abnormalities in chromatin dynamics, DNA methylation or sperm-borne RNAs may contribute to male infertility. In light of advances in deep sequencing technologies, researchers have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 162 publications
0
62
0
1
Order By: Relevance
“…Any exposure to a deleterious environment may change DNA methylation patterns in male germ cells and interfere with differentiation into functional sperm cells, ultimately impairing male fertility. In line with this, numerous studies in humans and model species have reported changes to sperm DNA methylation in the context of spermatogenesis defects, male infertility, and exposure to toxins or nutritional challenges (Boissonnas et al 2013;Schagdarsurengin and Steger 2016;McSwiggin and O'Doherty 2018).…”
Section: Introductionmentioning
confidence: 68%
“…Any exposure to a deleterious environment may change DNA methylation patterns in male germ cells and interfere with differentiation into functional sperm cells, ultimately impairing male fertility. In line with this, numerous studies in humans and model species have reported changes to sperm DNA methylation in the context of spermatogenesis defects, male infertility, and exposure to toxins or nutritional challenges (Boissonnas et al 2013;Schagdarsurengin and Steger 2016;McSwiggin and O'Doherty 2018).…”
Section: Introductionmentioning
confidence: 68%
“…Two recent meta‐analyses have linked human male obesity to reduced rates of clinical pregnancy and live births following ART, while a third found no evidence for a relationship between male BMI and treatment outcomes of ART . Negative effects of male obesity on embryo development have been detected in both human ART cohort studies and animal high‐fat diet studies, indicating that sperm can transmit detrimental factors to offspring that impair development . In addition, there is compelling evidence that offspring can inherit metabolic disease from their fathers via epigenetic mechanisms (reviewed in previous studies).…”
Section: Discussionmentioning
confidence: 99%
“…Establishment of totipotency is initiated upon fertilization with the formation of the zygote. differentiation into sperm, during which genomic DNA becomes transcriptionally silent, highly methylated, and packaged with protamines into a highly condensed configuration [33].…”
Section: Nucleolus Structures and Rrna Genes In Gametogenesismentioning
confidence: 99%